Smoking and alcohol by HPV status in head and neck cancer: a Mendelian randomization study - Thakral, Abhinav; Lee, John JW; Hou, Tianzhichao; Hueniken, Katrina; Dudding, Tom; Gormley, Mark; Virani, Shama; Olshan, Andrew; Diergaarde, Brenda; Ness, Andrew R.; Waterboer, Tim; Smith-Byrne, Karl; et al. (Nature communications, 2024)
HPV-positive and HPV-negative head and neck squamous cell carcinoma (HNSCC) are recognized as distinct entities. There remains uncertainty surrounding the causal effects of smoking and alcohol on the development of these two cancer types. Here we perform multivariable Mendelian randomization (MR) to evaluate the causal effects of smoking and alcohol on the risk of HPV-positive and HPV-negative HNSCC in 3431 cases and 3469 controls. Lifetime smoking exposure, as measured by the Comprehensive Smoking Index (CSI), is associated with increased risk of both HPV-negative HNSCC (OR = 3.03, 95%CI:1.75-5.24, P = 7.00E-05) and HPV-positive HNSCC (OR = 2.73, 95%CI:1.39-5.36, P = 0.003). Drinks Per Week is also linked with increased risk of both HPV-negative HNSCC (OR = 7.72, 95%CI:3.63-16.4, P = 1.00E-07) and HPV-positive HNSCC (OR = 2.66, 95%CI:1.06-6.68, P = 0.038). Smoking and alcohol independently increase the risk of both HPV-positive and HPV-negative HNSCC. These findings have important implications for understanding the modifying risk factors between HNSCC subtypes. Head and neck squamous cell carcinoma can occur with and without the presence of HPV infection. Here, the authors utilise Mendelian randomization to assess the causal effects of smoking and alcohol on HPV-positive and HPV-negative head and neck cancer development.